Avoidable Deaths A Systems Failure Approach to Disaster Risk Management - Ray-Bennett, Nibedita S. (SpringerBriefs in Environmental Science,, 2018)
This book addresses one of the most fundamental questions of the 21st century: why deaths continue to occur in natural disasters despite the tremendous advancements in disaster management science and weather forecasting systems, increased sophistication of human-built environments and ongoing economic and policy development worldwide. By presenting an interdisciplinary tool for analysing 'systems failure', the book provides concrete suggestions on how deaths may be reduced in resource-poor contexts. It goes beyond traditional risk and vulnerability perspectives and demonstrates that deaths in disasters are complex problems that can be solved by adopting a socio-technical perspective to improve current disaster management systems in the developing world. The book is a timely contribution, as it directly addresses Global Target One of the UN's 'Sendai Framework for Disaster Risk Reduction', which has urged 185 UN Member States to reduce disaster mortality by 2030. Further, it offers a valuable resource for students, researchers, policy-makers and practitioners interested in disaster risk reduction, human rights, gender, sociology of risk, crisis and disasters, environmental science, organisation and management studies.